2018
DOI: 10.1055/s-0037-1609482
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free С–С Coupling of 5,7-Dihydroxybenzopyrones with Quinoxalones and Pteridinones

Abstract: A new synthetic protocol for nucleophilic substitution of hydrogen­ in quinoxalones and pteridinones by the action of 5,7-di­hydroxycoumarins and related m-dihydroxybenzene compounds has been developed. The C–C coupling reaction proved to proceed smoothly under rather mild conditions, thus giving the corresponding C–H functionalized products in good yields. The advantages of this environmentally benign protocol are high regio- and chemoselectivity, and an easy workup procedure. Direct incorporation of the coum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…For instance, Khalymbadzha and co-workers developed a novel synthetic protocol for the nucleophilic substitution of hydrogen in quinoxalones and pteridones by using 5,7dihydroxycoumarins. [91] Cross-coupling reactions proceeded under mild conditions exclusively at the C8 position of the coumarin system and resulted in the formation of pyrazine-coumarin hybrid compounds. In the case of 7-nitro-quinoxalone, the S N H products were obtained in moderate yields via a two-step procedure consisting of the addition of 5,7-dihydroxycoumarin to the double bond of 7-nitro-quinoxalone (Scheme 35i) and the subsequent oxidation of the corresponding σ Hadducts with p-chloranil in DMF (Scheme 35ii).…”
Section: Cdc Reaction Of Phenols With π-Deficient Heterocyclesmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Khalymbadzha and co-workers developed a novel synthetic protocol for the nucleophilic substitution of hydrogen in quinoxalones and pteridones by using 5,7dihydroxycoumarins. [91] Cross-coupling reactions proceeded under mild conditions exclusively at the C8 position of the coumarin system and resulted in the formation of pyrazine-coumarin hybrid compounds. In the case of 7-nitro-quinoxalone, the S N H products were obtained in moderate yields via a two-step procedure consisting of the addition of 5,7-dihydroxycoumarin to the double bond of 7-nitro-quinoxalone (Scheme 35i) and the subsequent oxidation of the corresponding σ Hadducts with p-chloranil in DMF (Scheme 35ii).…”
Section: Cdc Reaction Of Phenols With π-Deficient Heterocyclesmentioning
confidence: 99%
“…However, in the case of pteridin-4-one (R=H), the oxidative coupling products were obtained in moderate yields via a one-step reaction involving TFA. [91] Khalymbadzha et al [92] showed that 5,7-dihydroxycoumarins can undergo nucleophilic addition to sand as-triazines in the same manner as diazines [91] to form stable σ H -adducts in yields of up to 97%. p-Chloranil enabled the aromatisation of the dihydrotriazine σ H -adducts, affording the oxidative coupling products in good yields.…”
Section: Cdc Reaction Of Phenols With π-Deficient Heterocyclesmentioning
confidence: 99%
See 3 more Smart Citations